Example of Implementation of the Human Attitude of the Head of Police and WH Syabri S.Pd and Partners to Turn Challenges Into Opportunities in the Millenial Age of Students of SMA Negeri 1 Blangkejeren - Yusuf Hanafi Pasaribu; Yulkarnaini Siregar; July Esther; Dewi Robiyanti; Syabri Syabri (Budapest International Research and Critics University, 2022)
The operational implementation of Public Order and Order (Trantibum) carried out by the Regency/Municipal Civil Service Police Unit (Satpol PP) in Blangkejeren must be based on a humane and authoritative attitude. To improve the image, Satpol PP must have a sense of humanity and authority in carrying out their duties.